Rituximab Followed by Belimumab Controls Severe Lupus Nephritis and Bullous Pemphigoid in Systemic Lupus Erythematosus Refractory to Several Combination Therapies - Petricca, Luca; Gigante, Maria Rita; Paglionico, Annamaria; Costanzi, Stefano; Vischini, Gisella; Di Mario, Clara; Varriano, Valentina; Tanti, Giacomo; Tolusso, Barbara; Alivernini, Stefano; Grandaliano, Giuseppe; Ferraccioli, Gianfranco; et al. (Frontiers in Medicine, 2020)
Systemic lupus erythematosus (SLE) and Bullous Pemphigoid (BP) are chronic autoimmune diseases in which B cells play an important pathogenic role in the different stages of the disease. B cell-targeted therapies have been suggested as a new rational approach for treating SLE. Rituximab (RTX), an anti-CD20 chimeric monoclonal antibody, failed to achieve primary endpoints in two clinical trials (EXPLORER and LUNAR) despite multiple observational and retrospective studies showed its beneficial effect on SLE. Moreover, RTX is recommended in cases of BP not responsive to conventional treatments. Belimumab (BLM), a human immunoglobulin G1 λ monoclonal antibody that inhibits soluble B-lymphocyte stimulator (BlyS)/B-cell activating factor (BAFF), is the only biological treatment approved for standard therapy of refractory autoantibody-positive active SLE. Animal models and few case reports support the efficacy of the combined use of RTX followed by BLM as maintenance therapy in severe Lupus Nephritis (LN) suggesting that their combined use may be more effective than their single use, without compromising safety. In this study, we describe the clinical case of a SLE patient with predominant renal involvement in overlap with BP, refractory to conventional therapy including RTX alone, achieving significant steroid sparing and clinical remission under sequential treatment of RTX-BLM. Moreover, we describe here the first case of BP successfully treated with BLM. This case report may encourage further clinical research studies in B lymphocytes target combination therapy in patients affected by SLE with major organ involvement or with refractory disease suggesting that RTX and BLM sequential therapy may be a valid option for the treatment of SLE manifestations-including conventional therapy and RTX resistant-LN.